Impact of Air Exposure on Vasotocinergic and Isotocinergic Systems in Gilthead Sea Bream (Sparus aurata): New Insights on Fish Stress Response - Skrzynska, Arleta K.; Maiorano, Elisabetta; Bastaroli, Marco; Naderi, Fatemeh; Míguez, Jesús M.; Martínez-Rodríguez, Gonzalo; Mancera, Juan M.; Martos-Sitcha, Juan A. (Frontiers in Physiology, 2018)
The hypothalamus-pituitary-interrenal (HPI) and hypothalamus-sympathetic-chromaffin cell (HSC) axes are involved in the regulation of the stress response in teleost. In this regard, the activation of a complex network of endocrine players is needed, including corticotrophin-releasing hormone (Crh), Crh binding protein (Crhbp), proopiomelanocortin (Pomc), thyrotropin-releasing hormone (Trh), arginine vasotocin (Avt) and isotocin (It) to finally produce pleiotropic functions. We aimed to investigate, using the gilthead sea bream (Sparus aurata) as a biological model, the transcriptomic response of different endocrine factors (crh, crhbp, pomcs, trh), neuropeptides (avt and it), and their specific receptors (avtrv1a, avtrv2 and itr) in four important target tissues (hypothalamus, pituitary, kidney and liver), after an acute stress situation. We also investigated several stress hormones (catecholamines and cortisol). The stress condition was induced by air exposure for 3 min, and hormonal, metabolic and transcriptomic parameters were analyzed in a time course response (15 and 30 min, and 1, 2, 4 and 8 h post-stress) in a total of 64 fish (n = 8 fish per experimental group; p-value = 0.05; statistical power = 95%). Our results showed that plasma noradrenaline, adrenaline and cortisol values increased few minutes after stress exposure. At hypothalamic and hypophyseal levels, acute stress affected mRNA expression of all measured precursors and hormonal factors, as well as their receptors (avtrs and itr), showing the activation, at central level, of HPI, HSC and Avt/It axes in the acute stress response. In addition, stress response also affected mRNA levels of avtrs and itr in the head kidney, as well as the steroidogenic acute regulatory protein (star) and tyrosine hydroxylase (th) expression, suggesting their participation in the HPI and HSC axes activation. Moreover, the pattern of changes in hepatic avtrs and itr gene expression also highlights an important role of vasotocinergic and isotocinergic pathways in liver metabolic organization after acute stress events. Our results demonstrate, both at transcriptional and circulating levels of several hormones, the existence of a complex activation of different endocrine pathways in S. aurata related to the stress pathways, where vasotocinergic and isotocinergic systems can also be considered key players of the acute stress response orchestration.